Binary Pd/amorphous-SrRuO3 hybrid film for high stability and fast activity recovery ethanol oxidation electrocatalysis. (January 2020) - Wu, Xiaoqiang; He, Jingxuan; Zhang, Meng; Liu, Zhongran; Zhang, Sa; Zhao, Yang; Li, Tian; Zhang, Fapei; Peng, Zheng; Cheng, Ningyan; Zhang, Jiaye; Wen, Xiaojian; et al.
Abstract: Pd- or Pt-based precious catalysts (PPC) are considered to be the best candidates toward high performance directly ethanol fuel cells (DEFC) applications, owing to their high intrinsic activity for ethanol oxidation reaction (EOR). However, the current major barrier for their commercialization is incompletely oxidized intermediates (IOI, such as CO) that poison the catalysts to affect the durability of the cells. Meanwhile, deactivated PPC catalyst is difficult to be recycled, thus impairing the economic benefits for the commercial applications. Moreover, because of the side effects of additive corrosion and aging, the carbon and organic binders widely used in current catalyst design would make the interactions of the IOI more complex to accelerate activity loss. Here, we report a Pd/amorphous SrRuO3 (Pd/a-SrRuO3 ) hybrid film as a promising material to overcome these problems. Perovskite SrRuO3 can effectively generate oxygen-contains (*OH, *OOH) for intermediates oxidation, providing an ideal platform to promote self-cleaning of CO on Pd activity sites. On the other hand, in analogy to typical self-adapting effect of amorphous catalyst in oxygen reduction reaction process, metastable state of amorphous SrRuO3 in this work is expected to prolong the activity adaptation region at the initial stage of cycling. Furthermore, our conceptual framework of directly depositing Pd/a-SrRuO3 film on operational electrode provides an effective solution to avoid the side effects related with carbon and binders, leading to superior reactivation phenomena with 98% efficiency. As a result, our designed Pd/a-SrRuO3 hybrid film exhibits superior EOR activity (4.0 A mg-1 Pd), durability (i-t, 60, 000s), self-adapting region (exceeding 400 cycles with ending activity of 3.0 A mg-1 Pd at 1000th cycle), and also a long-term operation (CP) up to 300, 000s with 10 times reactivation. This demonstration of a Pd/Pt-based hybrid catalyst with dual-capability of self-cleaning and self-adapting characteristics is an important step towards the development of highly durable EOR catalysts, with an enormous potential to promote practical application of DEFC. Graphical abstract: We have developed a facile and versatile strategy towards high stability and fast activity recovery ethanol oxidation electrocatalysis using Pd/amorphous SrRuO3 hybrid film via paused layer deposition technology (PLD). This binder- and carbon-free film endow the Pd/amorphous SrRuO3 anode catalyst with self-adapting, self-cleaning and reactivation properties. These properties significantly enhanced the EOR durability and first prolonged the long-term operation time to 30, 0000s. Image 1 Highlights: A carbon- and binder-free Pd/a-SrRuO3 film has been designed and used as a novel ethanol oxidation catalyst. This hybrid film possess high oxygen-contains generation activity for CO oxidation. The amorphous SrRuO3 has been demonstrated have a self-adapting behavior for EOR. This hybrid film possess an exciting durability of 300, 000s, which surpassed the records of current Pt/Pd based catalysts.